Implication of pulmonary hypertension in patients undergoing MitraClip therapy: results from the German transcatheter mitral valve interventions (TRAMI) registry. (24th July 2017) - Tigges, Eike; Blankenberg, Stefan; von Bardeleben, R. Stephan; Zürn, Christine; Bekeredjian, Raffi; Ouarrak, Taoufik; Sievert, Horst; Nickenig, Georg; Boekstegers, Peter; Senges, Jochen; Schillinger, Wolfgang; Lubos, Edith
Abstract: Aims: We sought to evaluate the impact of pulmonary hypertension on outcomes following MitraClip therapy. Methods and results: The 643 patients in the TRAnscatheter Mitral valve Interventions (TRAMI) registry were divided into three groups according to echocardiographically graded systolic pulmonary artery pressure (sPAP) (Group 1: patients with sPAP of ≤36 mmHg; Group 2: patients with sPAP of 37–50 mmHg; Group 3: patients with sPAP of >50 mmHg) and followed for 1 year. Recent cardiac decompensation, aortic valve disease and tricuspid valve insufficiency were observed more frequently in patients with higher sPAP. Furthermore, logEuroSCORE, Society of Thoracic Surgeons score and age were higher with rising sPAP values. No differences were observed in mitral regurgitation (MR) severity, co‐morbidities or clinical findings (New York Heart Association class, 6‐min walking distance). Reduction to MR of grade 1 or lower was achieved more often in patients with lower sPAP levels ( P  = 0.01). In Groups 2 and 3, sPAP was reduced significantly. Major adverse cardiac or cardiovascular events (MACCEs) occurring in hospital (death, myocardial infarction, stroke; <4% in each group), as well as 30‐day rates of MACCEs (6.1% in Group 1, 11.9% in Group 2, 12.4% in Group 3) and rehospitalization (18.9% in Group 1, 24.8% in Group 2, 24.8% in Group 3) did not differ significantly. At 1 year, differences in rates of mortality and MACCEs (20.3% in Group 1, 33.1% in Group 2, 34.7% in Group 3; P  < 0.01) were significant. Both Groups 2 [hazard ratio (HR) 1.81, P  = 0.0122] and 3 (HR 1.85, P  = 0.0092) were independently predictive of death. Rehospitalization rates did not differ during follow‐up. Conclusions: Despite higher mortality in patients with elevated sPAP, these data suggest the safety, feasibility and benefit of MitraClip therapy even in advanced stages of disease. An early approach might prevent the progress of pulmonary hypertension and improve outcomes.